2015
DOI: 10.1158/0008-5472.can-14-2464
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Semaphorin-3C Is an Inhibitor of Tumor Lymphangiogenesis and Metastasis

Abstract: Semaphorins play important regulatory roles in diverse processes such as axon guidance, angiogenesis, and immune responses. We find that semaphorin-3C (sema3C) induces the collapse of the cytoskeleton of lymphatic endothelial cells (LEC) in a neuropilin-2-, plexin-D1-, and plexin-A1-dependent manner, while most other semaphorins, including antiangiogenic semaphorins such as sema3A do not. Sema3C is cleaved, like other class-3 semaphorins, by furin-like pro-protein convertases (FPPC). Cleaved sema3C (p65-Sema3C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 53 publications
(70 reference statements)
4
100
0
Order By: Relevance
“…For instance, soluble TNFa (sTNFa) induces necrocytosis, whereas membrane TNFa induces apoptosis and shows cytotoxicity, even in sTNFa-resistant tumor cells (40,41). It was recently reported that cleaved SEMA3C (p65-SEMA3C) is a protumorigenic factor but that full-length SEMA3C functions as an inhibitor of tumor angiogenesis, lymphangiogenesis, and lymphatic metastasis (17). Nevertheless, sSEMA4C promotes lymphangiogenesis, and our results also show that the inhibitory effect of blocking SEMA4C cleavage (by GM6001) on LECs was weaker than the effect of using SEMA4C siRNAs or a function-blocking antibody, suggesting that the effect of mSEMA4C on lymphangiogenesis is also promotional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, soluble TNFa (sTNFa) induces necrocytosis, whereas membrane TNFa induces apoptosis and shows cytotoxicity, even in sTNFa-resistant tumor cells (40,41). It was recently reported that cleaved SEMA3C (p65-SEMA3C) is a protumorigenic factor but that full-length SEMA3C functions as an inhibitor of tumor angiogenesis, lymphangiogenesis, and lymphatic metastasis (17). Nevertheless, sSEMA4C promotes lymphangiogenesis, and our results also show that the inhibitory effect of blocking SEMA4C cleavage (by GM6001) on LECs was weaker than the effect of using SEMA4C siRNAs or a function-blocking antibody, suggesting that the effect of mSEMA4C on lymphangiogenesis is also promotional.…”
Section: Discussionmentioning
confidence: 99%
“…Plexins A1-A4 have been described as transducers of antiangiogenic signals conveyed by class-3 semaphorins such as sema3F, while the SEMA4D-PlexinB1 has been known as a potent inducer of angiogenesis and is associated with poor prognosis in various solid tumors (15,16). Angiogenesis and lymphangiogenesis intersect in the regulation of tumor microenvironment, and several recent studies also suggested that semaphorins may affect lymphangiogenesis (17,18). Nevertheless, the knowledge about the role of the semaphorin-mediated regulation of tumor lymphangiogenesis is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulated of the cells by various internal and external factors activated NF-κB, promoting the expression of a series of anti-apoptotic genes. Previous studies have demonstrated that the NF-κB signaling pathway plays a crucial role in the development of various tumors (23)(24)(25). However, it remains unknown whether GA acts on ovarian cancer tumor cells by stimulating the NF-κB signaling pathway, to induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF-A binding domain of neuropilin-1 seems to be distinct from its semaphorin binding domain 59 and it was indeed observed that sema3A and sema3F inhibit VEGF induced activation of ERK1/2 without inhibition of VEGF induced auto-phosphorylation of the VEGFR2 receptor which associates with neuropilin-1 52,60 lending support to the structural observations. However, there is also evidence suggesting that some class-3 semaphorins may compete with VEGF family members for binding to neuropilins 61 and that post-translational modifications of semaphorins such as cleavage by furin like pro-protein convertases 62 may modulate their neuropilin binding ability and their ability to complete with VEGFs for binding to neuropilins. 63 Interestingly, it is not clear if the binding of VFGF to neuropilins is required for the enhancement of VEGF induced signal transduction.…”
Section: Neuropilinsmentioning
confidence: 99%
“…Interestingly, some semaphorins such as sema3C, sema6A and sema3E display dual activities and have been characterized in some publications as inducers of tumor progression 108,[111][112][113][114] and in other publications as inhibitors of tumor progression. 61,92,115,116 The mechanisms responsible for this duality are not yet completely clear and are likely the result of post translational processing and the formation of complex associations between semaphorin receptors and other types of membrane bound receptors such as various tyrosinekinase receptors and adhesion receptors.…”
Section: Semaphorins As Regulators Of Tumor Progressionmentioning
confidence: 99%